Pemantauan dan Pengelolaan Sampah di Area Wisata Sukamakmur Jonggol Kabupaten Bogor Berbasis Web - Sugiyono; Arham; Al Faruq, Abdullah; Aziz, Naufal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Waste monitoring and management in tourist areas based on a website is an innovative solution to maintain cleanliness and the beauty of tourism environments. This system is designed to assist tourism managers in monitoring trash bin conditions in real-time and efficiently managing waste handling data. Currently, waste management in many tourist areas is still performed manually, making it less effective in maintaining optimal cleanliness. Therefore, the author developed a waste monitoring and management system based on a website using the Waterfall model. This system was built using the PHP programming language, the Laravel framework, and MySQL as the database. The system consists of two main dashboards: the admin dashboard and the staff dashboard. The admin dashboard features include managing trash bin data, scheduling waste collection, and generating waste management reports. Meanwhile, the staff dashboard is equipped with features for reporting trash bin conditions and scheduling waste collection. This system can be accessed via computer or mobile devices, providing flexible and efficient management. With this system, waste management in tourist areas is expected to become more structured, helping to maintain environmental cleanliness and enhance visitor comfort.